Analisa dan Usulan Perbaikan pada Area Produksi dengan Konsep 5s dan Safety di Unit Usaha Pabrik Es KUD. Mandiri Mina Fajar Sidik - Muhamad Taufiq Rachmat; Apid Hapid Maksum; Annisa Sabarina Rezki (Jurnal Ilmiah Wahana Pendidikan, 2022)
KUD. Mandiri Mina Fajar Sidik is a regional unit cooperative facility and infrastructure that focuses on the welfare of fishermen in supporting economic activities that become the livelihood of Blanakan Village, Subang Regency. One of the business units under the auspices of KUD. Mandiri Mina Fajar Sidik is the Ice Factory which is the location of this research. Based on observations, there is still a lack of awareness of workers in increasing work productivity, work culture and work safety security so that it poses a risk to the safety of the workers themselves. The use of the 5S consept (Seiri, Seiton, Seiso, Seiketsu, and Setsuke) and Safety in this study one of which aims to facilitate the production process at the Ice Factory. This method is a work attitude application program that emphasizes the management of the physical condition of an organized workplace.